2016
DOI: 10.1523/jneurosci.3708-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

CD8+T Cells and Endogenous IL-10 Are Required for Resolution of Chemotherapy-Induced Neuropathic Pain

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN),ϩ T cells. In conclusion, we identified a novel mechanism for resolution of CIPN that requires CD8 ϩ T cells and endogenous IL-10. We propose that CD8 ϩ T cells increase DRG IL-10 receptor expression and that IL-10 suppresses the abnormal paclitaxel-induced spontaneous discharges by DRG neurons to promote recovery from CIPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
190
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 172 publications
(203 citation statements)
references
References 65 publications
10
190
3
Order By: Relevance
“…107 Conversely, intrathecal IL-10 gene therapy or the intrathecal administration of recombinant IL-10 has been shown to progressively reverse the allodynic state associated with paclitaxel treatment. 96,108 In vitro, IL-10 suppressed paclitaxel-induced spontaneous discharges in DRG neurons. 108 It is interesting to note that we recently found that spontaneous resolution of CIPN depends on endogenous IL-10 signaling; blocking IL-10 signaling through the intrathecal administration of a neutralizing antibody delayed recovery from CIPN.…”
Section: Contribution Of Nitro-oxidative Stress To Cipnmentioning
confidence: 99%
See 3 more Smart Citations
“…107 Conversely, intrathecal IL-10 gene therapy or the intrathecal administration of recombinant IL-10 has been shown to progressively reverse the allodynic state associated with paclitaxel treatment. 96,108 In vitro, IL-10 suppressed paclitaxel-induced spontaneous discharges in DRG neurons. 108 It is interesting to note that we recently found that spontaneous resolution of CIPN depends on endogenous IL-10 signaling; blocking IL-10 signaling through the intrathecal administration of a neutralizing antibody delayed recovery from CIPN.…”
Section: Contribution Of Nitro-oxidative Stress To Cipnmentioning
confidence: 99%
“…With respect to regulatory cytokines, oxaliplatin‐induced mechanohypersensitivity is associated with reduced levels of the anti‐inflammatory cytokines IL‐10 and IL‐4 in the spinal dorsal horn . Conversely, intrathecal IL‐10 gene therapy or the intrathecal administration of recombinant IL‐10 has been shown to progressively reverse the allodynic state associated with paclitaxel treatment . In vitro, IL‐10 suppressed paclitaxel‐induced spontaneous discharges in DRG neurons …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, IL4 and IL12-induced IL10-expressing CD8 T cells was shown to inhibit graft-versus-host disease in vivo, and suppressed naive and effector T cell activation and IgG/IgE production [32]. Interestingly, CD8 T cell-mediated IL10 was shown to resolve chemotherapy-induced neuropathic pain [33]. Hence, IL10 expression might serve multiple roles in CD8 T cells, and the function of IFNg/IL10-double positive CD8 T cells should be further investigated using animal models.…”
Section: Discussionmentioning
confidence: 99%